2015
DOI: 10.1016/j.vetimm.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent variation in innate immune responses to porcine epidemic diarrhea virus infection in suckling versus weaned pigs

Abstract: Porcine epidemic diarrhea (PED) is an enteric coronaviral infection that causes severe morbidity and mortality in suckling pigs, but less severe disease in older pigs. Consequently, it causes significant economic losses to the pork industry. There are limited studies on the innate immune responses to PED virus (PEDV) in pigs. The aims of our study were to investigate differences in innate immune responses to PEDV infection in suckling and weaned pigs and to examine if disease severity coincides with reduced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
1
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 83 publications
9
96
1
10
Order By: Relevance
“…In addition, Cao et al have proven in vitro that PDEV could inhibit the production of IFN-β in its infected porcine intestinal epithelial cells [28]. However, recently, Thavamathi et al have verified that suckling pigs infected with PEDV have a higher and earlier increase in serum IFNα [29], which may explain the upregulation of those ISG proteins in the present study. It is also known that IFN regulates the production of ISGs by activating the JAK-STAT signaling pathway [30].…”
Section: Discussionmentioning
confidence: 51%
“…In addition, Cao et al have proven in vitro that PDEV could inhibit the production of IFN-β in its infected porcine intestinal epithelial cells [28]. However, recently, Thavamathi et al have verified that suckling pigs infected with PEDV have a higher and earlier increase in serum IFNα [29], which may explain the upregulation of those ISG proteins in the present study. It is also known that IFN regulates the production of ISGs by activating the JAK-STAT signaling pathway [30].…”
Section: Discussionmentioning
confidence: 51%
“…The levels of IFNα, IL-6, IL-12, IL-22, and TNFα were quantitated by ELISA in the cell culture supernatants (for IFNα, IL-6, and TNFα) or the serum samples collected from the two PDCoV-inoculated Gn pigs 1-2 and the four mock-inoculated Gn pigs 3-6 at PID 1, as described previously (Annamalai et al, 2015;Azevedo et al, 2006;Chattha et al, 2013). Briefly, Nunc Maxisorp 96-well plates were coated with antiporcine IL-6 (0.75 μg/ml, goat polyclonal antibody), anti-porcine IL-12 (0.75 μg/ml, goat polyclonal antibody), anti-porcine IFNα (2.5 μg/ml, clone K9) (R&D systems, Minneapolis, MN), anti-porcine IL-22 (2.0 μg/ ml, rabbit polyclonal antibody), and anti-porcine TNFα (1.5 μg/ml, goat polyclonal antibody) (Kingfisher biotech, Saint Paul, MN) overnight at 4 ℃ or 37 ℃ (for IFN-α only).…”
Section: Gross and Histological Analysis And If Staining For The Detementioning
confidence: 99%
“…The porcine IFN-α detection antibody was biotinylated using a commercial kit, as described previously (Chattha et al, 2013). Plates were developed and cytokine concentrations were calculated, as previously described (Annamalai et al, 2015;Azevedo et al, 2006). The samples were tested in duplicate, and cytokine levels were expressed as the mean values.…”
Section: Gross and Histological Analysis And If Staining For The Detementioning
confidence: 99%
“…106 Type I IFN plays an important role in antiviral immune response; however, several recent reports showed that PEDV has the ability to suppress the IFN antiviral response for 45,[106][107][108][109] These in vitro studies have identified eleven viral proteins responsible for this suppression, which include nsp1, nsp3, nsp5, nsp7, nsp14, nsp15, nsp16, ORF3, E, M, and N. The molecular mechanisms of PEDV-inhibition Type I IFN production include: 1) papain-like proteinase 2 of PEDV antagonizing the IFN response by deubiquitinating retinoic acidinducible gene-I and stimulator of IFN genes; 107 2) PEDV N protein suppressing the IFN regulatory factor 3 (IRF3) and nuclear factor kappa-B activities and antagonizing the IFN-β production by disrupting the interaction between IRF3 and TANK-binding kinase 1; 45 3) PEDV infection in intestinal epithelial cells inhibiting dsRNA-mediated IFN-β induction by interfering with IRF3 activity associated with retinoic acid-inducible gene-I-mediated signaling pathway; 108 4) PEDV nsp1 interrupting the enhanceosome assembly of IRF3 and cAMP response element binding protein by degrading CREB-binding protein via the proteasomedependent pathway; 106 and 5) PEDV-encoded 3C-like protease (nsp5)-mediated proteolytic cleavage of NEMO directly being involved in inhibition of IFN-β transcription. 109 A report by Annamalai et al 110 showed that the innate immune responses to PEDV infection vary with the age of host. PEDV-infected suckling pigs had significantly lower natural killer (NK) cell frequencies, undetectable NK cell activity, and lower IFN-γ-producing NK cells in blood and ileum compared to PEDV-infected weaned pigs.…”
Section: Immune Responses To Pedv Infectionmentioning
confidence: 99%